2022
DOI: 10.1002/ccr3.6138
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to coal and risk of multiple health outcomes: A case report

Abstract: Occupational cutaneous squamous-cell carcinoma has an increased incidence, but rarely suspected. When located in an uncovered skin area, it is closely linked to polycyclic aromatic hydrocarbons exposure. However, single pulmonary anthracosis nodule is rarely described in the literature. The association of both diseases due to the same exposure remains uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Early investigations have shown that dermal exposure to PAHs is linked to several skin illnesses, such as acne, pigmentary diseases, aging, and cancer (Hakim et al, 2022). Nevertheless, the specific action mechanisms by which these chemicals (PAHs) exert their toxic effect on the skin are still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Early investigations have shown that dermal exposure to PAHs is linked to several skin illnesses, such as acne, pigmentary diseases, aging, and cancer (Hakim et al, 2022). Nevertheless, the specific action mechanisms by which these chemicals (PAHs) exert their toxic effect on the skin are still uncertain.…”
Section: Introductionmentioning
confidence: 99%